Uso da palha de carnaúba em revestimento de dutos - Fernandes, Jéssica Emanuela de Araújo (2011)
In this work, the plant species Copernicia prunifera (Miller) H. E. Moore (carnauba), naturally occurring which prevails in the northeast region of Brazil was the subject of studies aiming its use as external coating of pipelines used in petroleum industry. The part of the plant worked were the leaves, also called straw, which were coated with resinous material. For this purpose, it was necessary to evaluate the effectiveness of the use of acrylic resins in the straw carnauba coating. The properties of the untreated carnauba straw and chemically treated with sodium hydroxide, hexane and carbon tetrachloride were investigated by ATRFTIR, SEM and thermal analysis. The first two techniques showed that treatment with solvents has caused major changes in the straw surface, while the thermal analysis indicated that the sodium hydroxide caused variations in thermal stability of straw constituents. Water absorption measurements showed that treatments have accelerated the absorption process and the reduction of contact angle values for treated samples with solvents indicated higher hidrophilicity of straw. The tensile tests showed lower values of elastic modulus and tensile strength for treated samples. Furthermore, coatings using pure commercial resins A and B as well as the formulations with clay were applied in straw and they were examined once again through thermal analysis, water absorption measurements, contact angle and mechanical tests. To analyze the effect of heat ageing, samples were subjected to tensile tests again in order to assess its resistance. The results showed that the resins/clay formulations increased thermal stability of straw, they promoted a good impermeabilization and caused significant decrease in the values of elastic modulus and tensile strength. Evaluating the ageing effect on the mechanical properties, it has been showed good recovery to the coated straw with the formulations A 60 and A 80% in modulus and tensile strength values and elongation at break values have remained very close. It is thus concluded that the carnauba straw can be used as a coating of pipelines with significant cost savings, since there is no need for pretreatment for its use and shows itself as a viable biotechnology alternative, contributing to the quality of coatings material and environment preservation.